Microporous building material and preparation method thereof

By introducing microporous structures into building materials and using a combination of composite foaming agent and modified epoxy resin, the problem of difficulty in achieving light weight and high strength at the same time in existing dry powder mortars is solved, and the effect of lightweight and high strength is achieved.

CN116462468BActive Publication Date: 2025-04-18JIANGSU XUNWEI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310438794.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-23
Publication Date
2025-04-18
Estimated Expiration
2043-04-23

AI Technical Summary

Technical Problem

When existing dry powder mortar is used in construction, it is difficult to achieve the effect of light material quality and high strength at the same time.

Method used

Using a microporous building material, which includes silicate cement, mineral blends, sodium-based bentonite, composite foaming agent, composite perlite, regenerated fibers and calcium oxide, the microporous structure is formed by introducing modified epoxy resin and sodium bicarbonate during the preparation of the composite foaming agent.

Benefits of technology

While ensuring mechanical strength, the weight of the material is reduced while introducing a large number of microporous structures, and the effect of lightweight and high strength is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004193109230000021
    Figure BDA0004193109230000021
  • Figure BDA0004193109230000022
    Figure BDA0004193109230000022
  • Figure BDA0004193109230000023
    Figure BDA0004193109230000023
Patent Text Reader

Abstract

The invention discloses a microporous building material and a preparation method thereof. The microporous building material comprises the following raw materials in parts by weight: 100-150 parts of Portland cement, 50-100 parts of mineral admixture, 1-5 parts of sodium bentonite, 2-3.5 parts of composite foaming agent, 10-12 parts of composite perlite, 3-5 parts of regenerated fiber and 3-5 parts of calcium oxide; the Portland cement, the mineral admixture, the sodium bentonite, the composite foaming agent, the composite perlite and the regenerated fiber are uniformly stirred at high speed to obtain dry mortar, and water is added during on-site construction and stirred to obtain the microporous building material; when the composite foaming agent is actually used, the modified epoxy resin on the surface is dissolved when it meets water, and sodium bicarbonate is leaked out, which serves as an inorganic pore-forming agent and releases a small amount of fine bubbles to form a large number of micropores, so as to obtain the lightweight microporous building material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, in particular to a microporous building material and a preparation method thereof. Background Art

[0002] Dry-mix mortar refers to a granular or powdery material made by physically mixing dried and sieved aggregates (such as quartz sand), inorganic cementitious materials (such as cement) and additives (such as polymers) in a certain proportion. It is transported to the construction site in bags or bulk and can be used directly after adding water and mixing. It is also called dry mortar, dry-mixed mortar, and dry-mixed powder. Some building adhesives also belong to this category. Dry-mix mortar plays a bonding, cushioning, protective and decorative role in the construction industry in a thin layer. It is widely used in construction and decoration projects. How to control the building materials prepared with dry-mix mortar to have the advantages of light weight and high strength is a technical problem that urgently needs to be solved. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a microporous building material and a preparation method thereof.

[0004] The purpose of the present invention can be achieved by the following technical solutions:

[0005] A microporous building material, comprising the following raw materials in parts by weight: 100-150 parts of Portland cement, 50-100 parts of mineral admixture, 1-5 parts of sodium bentonite, 2-3.5 parts of composite foaming agent, 10-12 parts of composite perlite, 3-5 parts of regenerated fiber, and 3-5 parts of calcium oxide;

[0006] The composite foaming agent comprises the following steps:

[0007] Step S1, adding epoxy resin, toluene diisocyanate and butanone into a three-necked flask, heating to 50-55° C., stirring at a uniform speed and reacting for 2 hours, and obtaining intermediate 1 after the reaction is completed, wherein the molar ratio of the hydroxyl group on the epoxy resin to the toluene diisocyanate is controlled to be 1:1, and the amount of butanone used is 3-5 times the weight of the epoxy resin;

[0008] In step S1, butanone is used as a solvent, and the hydroxyl group on the epoxy resin reacts with an isocyanate group on toluene diisocyanate to generate an intermediate 1. The structure of the epoxy resin is shown below:

[0009]

[0010] The structure of intermediate 1 is shown below:

[0011]

[0012] Step S2, adding dimethylolpropionic acid and dibutyltin dilaurate, stirring at a uniform speed and heating to 80° C., reflux reaction, to obtain a modified epoxy resin, wherein the molar ratio of the isocyanate group on the intermediate 1 to the dimethylolpropionic acid is controlled to be 1:1, and the amount of dibutyltin dilaurate is 2-3% of the weight of the intermediate 1;

[0013] In step S2, dibutyltin dilaurate is used as a catalyst, and the isocyanate group on the intermediate 1 reacts with the hydroxyl group on the dimethylolpropionic acid to generate a modified epoxy resin, the structure of which is shown below:

[0014]

[0015] By using toluene diisocyanate as a medium, dimethylolpropionic acid is introduced into the epoxy resin structure. Dimethylolpropionic acid is used as a hydrophilic chain extender and is connected to the epoxy resin, thereby improving the water solubility of the epoxy resin.

[0016] Step S3, ball-milling sodium bicarbonate and passing through a 200-mesh sieve, then mixing sodium bicarbonate, modified epoxy resin and pentaerythritol tetramercapto ester, adding dichloromethane, stirring at a uniform speed to form a suspension, heating to 50-55° C., stirring at a uniform speed until the dichloromethane is completely evaporated, obtaining small particles, pouring the particles into a flask, using petroleum ether as a dispersion system, adding triethylamine, stirring at a uniform speed for 6 hours, filtering, washing, and drying to obtain a composite foaming agent, wherein the amount ratio of sodium bicarbonate, modified epoxy resin, pentaerythritol tetramercapto ester and dichloromethane is controlled to be 3-5 g: 0.5 g: 0.20-0.25 g: 20 mL, and the amount of triethylamine is 10-15% of the weight of the modified epoxy resin.

[0017] In step S3, pentaerythritol tetramercaptoester is used as a curing agent, dichloromethane is used as a solvent, sodium bicarbonate and a modified epoxy resin are mixed, and then the solvent is evaporated to obtain small particles. The small particles have a core-shell structure with a core of sodium bicarbonate and a surface of the modified epoxy resin. When the composite foaming agent is actually used, it encounters water and the modified epoxy resin on the surface dissolves, leaking out sodium bicarbonate, which acts as an inorganic pore-forming agent, releasing a small amount of fine bubbles to form a large number of micropores.

[0018] Furthermore: the mineral admixture is one or more of fly ash, kaolin and quartz sand powder mixed in any proportion.

[0019] Further: the composite perlite is prepared by the following steps:

[0020] Pour silica hydrosol into expanded perlite until the expanded perlite is submerged, then seal and evacuate, control the vacuum degree to -0.03 MPa, and obtain composite 1, then take out, vacuum filter composite 1 at -0.05 MPa for 1 min, then seal and let stand at room temperature for 4 hours to obtain composite 2, then continue to age for 24 hours, then dry at 40°C, 60°C, 80°C and 100°C for 4 hours respectively to obtain composite perlite, and control the weight ratio of silica hydrosol to expanded perlite to 20-25:1.

[0021] Furthermore: the regenerated fiber is any one of industrial textile waste fiber and yarn, and the length of the regenerated fiber is 2-3 cm.

[0022] A method for preparing a microporous building material comprises the following steps:

[0023] The silicate cement, mineral admixture, sodium-based bentonite, composite foaming agent, composite perlite and recycled fiber are uniformly mixed by high-speed stirring to obtain dry mortar, and water is added during on-site construction and stirred to obtain microporous building materials.

[0024] Beneficial effects of the present invention:

[0025] The microporous building material of the present invention uses dry powder mortar as a matrix. Water is added during on-site construction and stirred evenly to obtain the microporous building material. A composite foaming agent is synthesized in the preparation process. Butanone is used as a solvent. A hydroxyl group on an epoxy resin reacts with an isocyanate group on toluene diisocyanate to generate an intermediate 1. Then, under the condition of dibutyltin dilaurate as a catalyst, the isocyanate group on the intermediate 1 reacts with a hydroxyl group on dimethylol propionic acid to generate a modified epoxy resin. Pentaerythritol tetramercaptoester is used as a curing agent. Dichloromethane is used as a solvent. Sodium bicarbonate and the modified epoxy resin are mixed. Then, the solvent is evaporated and removed to obtain small particles. The small particles are a core-shell structure with sodium bicarbonate as an inner core and modified epoxy resin as a surface. When the composite foaming agent is used in practice, the modified epoxy resin on the surface dissolves when it encounters water, and sodium bicarbonate leaks out. As an inorganic pore-forming agent, a small amount of fine bubbles are released to form a large number of micropores, thereby obtaining a lightweight microporous building material. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] The composite foaming agent comprises the following steps:

[0029] Step S1, adding epoxy resin, toluene diisocyanate and butanone into a three-necked flask, heating to 50° C., stirring at a constant speed and reacting for 2 hours, and obtaining intermediate 1 after the reaction, wherein the molar ratio of the hydroxyl group on the epoxy resin to the toluene diisocyanate is controlled to be 1:1, and the amount of butanone is 3 times the weight of the epoxy resin;

[0030] Step S2, adding dimethylolpropionic acid and dibutyltin dilaurate, stirring at a uniform speed and heating to 80° C., reflux reaction, to obtain a modified epoxy resin, wherein the molar ratio of the isocyanate group on the intermediate 1 to the dimethylolpropionic acid is controlled to be 1:1, and the amount of dibutyltin dilaurate is 2% of the weight of the intermediate 1;

[0031] Step S3, ball-milling sodium bicarbonate and passing through a 200-mesh sieve, then mixing sodium bicarbonate, modified epoxy resin and pentaerythritol tetramercapto ester, adding dichloromethane, stirring at a uniform speed to form a suspension, heating to 50° C., stirring at a uniform speed until the dichloromethane is completely evaporated, obtaining small particles, pouring the particles into a flask, using petroleum ether as a dispersion system, adding triethylamine, stirring at a uniform speed for 6 hours, filtering, washing, and drying to obtain a composite foaming agent, wherein the amount ratio of sodium bicarbonate, modified epoxy resin, pentaerythritol tetramercapto ester and dichloromethane is controlled to be 3g:0.5g:0.20g:20mL, and the amount of triethylamine is 10% of the weight of the modified epoxy resin.

[0032] Example 2

[0033] The composite foaming agent comprises the following steps:

[0034] Step S1, adding epoxy resin, toluene diisocyanate and butanone into a three-necked flask, heating to 52° C., stirring at a constant speed and reacting for 2 hours, and obtaining intermediate 1 after the reaction, wherein the molar ratio of the hydroxyl group on the epoxy resin to the toluene diisocyanate is controlled to be 1:1, and the amount of butanone is 4 times the weight of the epoxy resin;

[0035] Step S2, adding dimethylolpropionic acid and dibutyltin dilaurate, stirring at a uniform speed and heating to 80° C., reflux reaction, to obtain a modified epoxy resin, wherein the molar ratio of the isocyanate group on the intermediate 1 to the dimethylolpropionic acid is controlled to be 1:1, and the amount of dibutyltin dilaurate is 2.5% of the weight of the intermediate 1;

[0036] Step S3, ball-milling sodium bicarbonate and passing through a 200-mesh sieve, then mixing sodium bicarbonate, modified epoxy resin and pentaerythritol tetramercapto ester, adding dichloromethane, stirring at a uniform speed to form a suspension, heating to 53° C., stirring at a uniform speed until the dichloromethane is completely evaporated, obtaining small particles, pouring the particles into a flask, using petroleum ether as a dispersion system, adding triethylamine, stirring at a uniform speed for 6 hours, filtering, washing, and drying to obtain a composite foaming agent, wherein the amount ratio of sodium bicarbonate, modified epoxy resin, pentaerythritol tetramercapto ester and dichloromethane is controlled to be 4g:0.5g:0.24g:20mL, and the amount of triethylamine is 12% of the weight of the modified epoxy resin.

[0037] Example 3

[0038] The composite foaming agent comprises the following steps:

[0039] Step S1, adding epoxy resin, toluene diisocyanate and butanone into a three-necked flask, heating to 55° C., stirring at a constant speed and reacting for 2 hours, and obtaining intermediate 1 after the reaction, wherein the molar ratio of the hydroxyl group on the epoxy resin to the toluene diisocyanate is controlled to be 1:1, and the amount of butanone is 5 times the weight of the epoxy resin;

[0040] Step S2, adding dimethylolpropionic acid and dibutyltin dilaurate, stirring at a uniform speed and heating to 80° C., reflux reaction, to obtain a modified epoxy resin, wherein the molar ratio of the isocyanate group on the intermediate 1 to the dimethylolpropionic acid is controlled to be 1:1, and the amount of dibutyltin dilaurate is 3% of the weight of the intermediate 1;

[0041] Step S3, ball-milling sodium bicarbonate and passing through a 200-mesh sieve, then mixing sodium bicarbonate, modified epoxy resin and pentaerythritol tetramercapto ester, adding dichloromethane, stirring at a uniform speed to form a suspension, heating to 55° C., stirring at a uniform speed until the dichloromethane is completely evaporated, obtaining small particles, pouring them into a flask, using petroleum ether as a dispersion system, adding triethylamine, stirring at a uniform speed for 6 hours, filtering, washing, and drying to obtain a composite foaming agent, wherein the amount ratio of sodium bicarbonate, modified epoxy resin, pentaerythritol tetramercapto ester and dichloromethane is controlled to be 5g:0.5g:0.25g:20mL, and the amount of triethylamine is 15% of the weight of the modified epoxy resin.

[0042] Example 4

[0043] The composite perlite comprises the following steps:

[0044] Pour silica hydrosol into expanded perlite until the expanded perlite is submerged, then seal and evacuate, control the vacuum degree to -0.03 MPa, and obtain composite 1. Then take out and vacuum filter composite 1 at -0.05 MPa for 1 min, then seal and let stand at room temperature for 4 h to obtain composite 2, then continue to age for 24 h, and then dry at 40°C, 60°C, 80°C and 100°C for 4 h respectively to obtain composite perlite, and control the weight ratio of silica hydrosol to expanded perlite to 20:1.

[0045] Example 5

[0046] The composite perlite comprises the following steps:

[0047] Pour silica hydrosol into expanded perlite until the expanded perlite is submerged, then seal and evacuate, control the vacuum degree to -0.03 MPa, and obtain composite 1, then take out, vacuum filter composite 1 at -0.05 MPa for 1 min, then seal and let stand at room temperature for 4 h to obtain composite 2, then continue to age for 24 h, then dry at 40°C, 60°C, 80°C and 100°C for 4 h respectively to obtain composite perlite, and control the weight ratio of silica hydrosol to expanded perlite to 25:1.

[0048] Example 6

[0049] A microporous building material, comprising the following raw materials in parts by weight: 100 parts of silicate cement, 50 parts of quartz sand powder, 1 part of sodium bentonite, 2 parts of composite foaming agent, 10 parts of composite perlite, 3 parts of regenerated fiber, and 3 parts of calcium oxide;

[0050] The silicate cement, quartz sand powder, sodium-based bentonite, composite foaming agent, composite perlite and recycled fiber are mixed evenly at high speed to obtain dry mortar, and water is added during on-site construction and mixed evenly to obtain microporous building materials.

[0051] Example 7

[0052] A microporous building material, comprising the following raw materials by weight: 120 parts of silicate cement, 80 parts of fly ash, 3 parts of sodium bentonite, 3 parts of composite foaming agent, 11 parts of composite perlite, 4 parts of regenerated fiber, and 4 parts of calcium oxide;

[0053] The silicate cement, fly ash, sodium-based bentonite, composite foaming agent, composite perlite and recycled fiber are uniformly mixed by high-speed stirring to obtain dry mortar, and water is added during on-site construction and stirred to obtain microporous building materials.

[0054] Example 8

[0055] A microporous building material, comprising the following raw materials in parts by weight: 150 parts of silicate cement, 100 parts of kaolin, 5 parts of sodium bentonite, 3.5 parts of composite foaming agent, 12 parts of composite perlite, 5 parts of regenerated fiber, and 5 parts of calcium oxide;

[0056] The silicate cement, kaolin, sodium-based bentonite, composite foaming agent, composite perlite and regenerated fiber are uniformly mixed by high-speed stirring to obtain dry mortar, and water is added during on-site construction and stirred to obtain microporous building materials.

[0057] Comparative Example 1

[0058] Compared with Example 6, this comparative example uses sodium bicarbonate instead of the composite foaming agent.

[0059] Comparative Example 2

[0060] This comparative example is a commercially available silicate cement-based building material.

[0061] The building materials prepared in Examples 6-8 and Comparative Examples 1-2 were cast into cubes of 2mX2mX0.25m, and their compressive strength and splitting strength were measured (using a SYE-2000 pressure testing machine). The results are shown in the following table:

[0062] Water permeability: Slowly pour water into the cubic concrete blocks and record the changes in the mass of the concrete blocks after 5min and 30min.

[0063]

[0064] It can be seen from the above table that the microporous building material prepared in the embodiment of the present invention introduces a large number of microporous structures into the structure while ensuring the mechanical strength, thereby reducing the weight and achieving the effect of light weight and high strength.

[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A microporous building material, characterized in that: The invention comprises the following raw materials in parts by weight: 100-150 parts of silicate cement, 50-100 parts of mineral admixture, 1-5 parts of sodium bentonite, 2-3.5 parts of composite foaming agent, 10-12 parts of composite perlite, 3-5 parts of recycled fiber and 3-5 parts of calcium oxide; The composite foaming agent comprises the following steps: Step S1, adding epoxy resin, toluene diisocyanate and butanone into a three-necked flask, heating to 50-55° C., stirring at a uniform speed and reacting for 2 hours, and obtaining intermediate 1 after the reaction is completed, wherein the molar ratio of the hydroxyl group on the epoxy resin to the toluene diisocyanate is controlled to be 1:1, and the amount of butanone used is 3-5 times the weight of the epoxy resin; Step S2, adding dimethylolpropionic acid and dibutyltin dilaurate, stirring at a uniform speed and heating to 80° C., reflux reaction, to obtain a modified epoxy resin, wherein the molar ratio of the isocyanate group on the intermediate 1 to the dimethylolpropionic acid is controlled to be 1:1, and the amount of dibutyltin dilaurate is 2-3% of the weight of the intermediate 1; Step S3, ball-milling sodium bicarbonate and passing it through a 200-mesh sieve, then mixing sodium bicarbonate, modified epoxy resin and pentaerythritol tetramercapto ester, adding dichloromethane, stirring at a uniform speed to form a suspension, heating to 50-55° C., stirring at a uniform speed until the dichloromethane is completely evaporated, obtaining small particles, pouring them into a flask, using petroleum ether as a dispersion system, adding triethylamine, stirring at a uniform speed for 6 hours, filtering, washing, and drying to obtain a composite foaming agent, wherein the amount ratio of sodium bicarbonate, modified epoxy resin, pentaerythritol tetramercapto ester and dichloromethane is controlled to be 3-5g: 0.5g: 0.20-0.25g: 20mL, and the amount of triethylamine is 10-15% of the weight of the modified epoxy resin; The composite perlite comprises the following steps: Pour silica hydrosol into expanded perlite until the expanded perlite is submerged, then seal and evacuate, control the vacuum degree to -0.03 MPa, and obtain composite 1, then take out, vacuum filter composite 1 at -0.05 MPa for 1 min, then seal and let stand at room temperature for 4 h to obtain composite 2, then continue to age for 24 h, then dry at 40°C, 60°C, 80°C and 100°C for 4 h respectively to obtain composite perlite, and control the weight ratio of silica hydrosol to expanded perlite to 20-25:

1.

2. A microporous building material according to claim 1, characterized in that: The mineral admixture is one or more of fly ash, kaolin and quartz sand powder mixed in any proportion.

3. A microporous building material according to claim 1, characterized in that: The regenerated fiber is any one of industrial textile waste fiber and yarn, and the length of the regenerated fiber is 2-3 cm.

4. The method for preparing a microporous building material according to claim 1, characterized in that: The steps include: The silicate cement, mineral admixture, sodium-based bentonite, composite foaming agent, composite perlite and recycled fiber are uniformly mixed by high-speed stirring to obtain dry mortar, and water is added during on-site construction and stirred to obtain microporous building materials.

Citation Information

Patent Citations

  • Anti-haze gypsum wall material for prefabricated building and preparation method of anti-haze gypsum wall material

    CN109928709A

  • Incombustible composition and preparation method of incombustible material for architecture using the same

    KR100772124B1